(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Purpose. To identify specific risk factors and protective factors to inform tailored screening and management strategies for high-risk individuals. Methods. This case-control study included a total of 800 eyes from 400 individuals, comprising 200 pairs of eyes diagnosed with primary open-angle glaucoma (POAG) and 200 glaucoma-free (the control group). Data were collected through structured questionnaires and comprehensive ophthalmologic examinations. Statistical analyses were performed to assess the association between POAG and systemic conditions such as diabetes and hypertension, as well as various sociodemographic factors. Results. Systolic arterial hypertension was identified as a risk factor (p<0.05), while diastolic hypertension showed a protective effect (p<0.05). Contrary to expectations, diabetes mellitus was not statistically associated with an increased risk of POAG (p>0.05). Conclusion. The results emphasize the importance of arterial hypertension in the pathogenesis of POAG. The lack of significant association with diabetes in this cohort may be due to population-specific factors, such as genetic background or lifestyle. These findings support the need for tailored screening programs targeting individuals with risk factors. This study highlights the complex interaction of systemic diseases in the development of POAG. While arterial hypertension is confirmed risk factor, diabetes did not play a significant role in this cohort. Early detection through targeted screening of high-risk groups could improve the management and outcomes of glaucoma patients.